Ritual Mandi Pengantin: Kecemasan, Harapan dan Tafsir Simbolis tentang Masa Depan - Nurmasitah Nurmasitah; Muliono Muliono (Indonesian Journal of Religion and Society, 2021)
The ritual of bridal shower reflects a symbolic system and has a relation to the being, the sacred and the profane. Phenomenologically, this study is intended to discuss the ritual of bridal bathing. The approach used to reveal the ritual’s meaning is the interpretation of symbolic. This study used a qualitative. The social setting of this research was carried out in community of Banjar, in the Tambilahan, Indragiri Hilir. Data were collected through interviews, observation and documentation. This study shows that the bridal bath ritual has three fundamental aspects in which the ritual is practiced by Banjar community. First, as a culture heritization of the ancestors. Second, as a diealectic of feelings: fear and hope in the life of the bride family. Third, as a symbolic reflection of the sacred values. The bridal bath ritual on the sequel becomes a path for the brides and their families to spared the disturbance of the being or evil orchestra, repudiating the fear, the anxiety, and as a path of household resilience in the future.